Linear ODE with nonlocal boundary conditions and Green’s functions for such problems - Roman, Svetlana; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2010)
In this article we investigate a formula for the Green’s function for the n-orderlinear differential equation with n additional conditions. We use this formula for calculatingthe Green’s function for problems with nonlocal boundary conditions.
Keywords: Green’s function; nonlocal boundary conditions